Negative electrode sheet and preparation method thereof and battery

By using Na-K-M ternary alloy and porous material in sodium ion batteries to form a negative electrode sheet, the problem of low energy density of sodium ion batteries is solved, and higher energy density and good electrochemistry at low temperatures are achieved. performance.

CN119297208BActive Publication Date: 2025-02-25JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411697391.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Existing sodium ion batteries have low energy density, high manufacturing cost and unstable capacity of hard carbon materials.

Method used

A negative electrode active material layer including a Na-K-M ternary alloy is used to form a negative electrode sheet of a current collector and an negative electrode active material layer through a combination of a porous material and an alloy material. The alloy material has ultra-high surface tension and ultra-wide alloy molar ratio windows, which can remain liquid at lower temperatures.

Benefits of technology

Effectively inhibit sodium crystallization, broaden the liquid window, improve physical stability, increase energy density, and maintain good electrochemical performance at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to the field of new energy, and specifically to a negative electrode plate, a preparation method thereof, and a battery. The negative electrode plate of the present invention comprises a current collector and a negative electrode active material layer disposed on the surface of the current collector; the negative electrode active material layer comprises a porous material and an alloy material filled in the pores of the porous material; wherein the alloy material comprises a Na-K-M ternary alloy, and the metal element M contained in the Na-K-M ternary alloy is selected from one of the IIA group and the IIIA group. The negative electrode plate of the present invention is applied to lithium-ion batteries with significantly improved electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy, and in particular to a negative electrode sheet and a preparation method thereof, and a battery. Background Art

[0002] Lithium-ion batteries have become energy storage devices for electric vehicles and power tools due to their high energy density and convenience. However, both the positive electrode materials in lithium-ion batteries and the lithium salts in the electrolyte require lithium. Lithium resources are extremely unevenly distributed around the world and are extremely rare in nature, making them a rare metal. Therefore, the price of lithium ore is relatively high, which seriously affects the manufacturing cost of lithium-ion batteries. Therefore, it is urgent to find new energy storage devices to replace lithium-ion batteries.

[0003] Sodium-ion batteries use sodium ions as ion transport for electrochemical reactions. Since the ionic radius of sodium ions is larger than that of lithium ions, graphite cannot be used as the negative electrode material. In order to address the problem of low energy density of sodium-ion batteries, hard carbon materials with high gram capacity are currently used as negative electrodes. Although the interlayer spacing of hard carbon materials is high, which allows sodium ions to be embedded and detached, the gram capacity of hard carbon materials manufactured as negative electrode materials for sodium-ion batteries will vary greatly due to different raw materials, and the capacity is not superior to that of graphite. Summary of the invention

[0004] In view of this, the present invention is committed to providing a negative electrode plate and a preparation method thereof and a battery to solve the problem of low energy density of sodium ion batteries in the prior art.

[0005] In order to solve the above technical problems, this application is implemented as follows:

[0006] A first aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising a current collector and a negative electrode active material layer disposed on the surface of the current collector; the negative electrode active material layer comprises a porous material and an alloy material filled in the pores of the porous material;

[0007] Wherein, the alloy material comprises a Na-KM ternary alloy, and the metal element M contained in the Na-KM ternary alloy is selected from one of group IIA and group IIIA.

[0008] Optionally, the metal Na and metal K contained in the Na-KM ternary alloy satisfy the relationship: 0.2≤n1 / (n1+n2)≤0.9, wherein n1 represents the amount of the metal Na contained in the Na-KM ternary alloy, and n2 represents the amount of the metal K contained in the Na-KM ternary alloy; and / or, based on the total mass of the Na-KM ternary alloy, the content of the metal element M is 0.001~10wt.%; and / or, the metal element M is selected from one of Mg, Al, Ca, Sr, Ba and Ga.

[0009] Optionally, the viscosity of the Na-KM ternary alloy is 100~50000 Cp.

[0010] Optionally, based on the total mass of the negative electrode active material layer, the content of the porous material is 1-2 wt.%; and / or, the porous material is selected from at least one of ZnO, SnO, vermiculite and boehmite.

[0011] Optionally, a contact portion between the alloy material and the porous material has an oxide layer, and the oxide layer includes sodium oxide and / or potassium oxide.

[0012] A second aspect of the present invention provides a method for preparing a negative electrode sheet, the method comprising the following steps:

[0013] S1, coating a slurry containing a porous material on the surface of a current collector to obtain a current collector coated with the slurry; drying the current collector coated with the slurry to obtain a first pole piece;

[0014] S2, coating a liquid sodium-potassium alloy on a surface of the first pole piece away from the current collector to obtain a second pole piece;

[0015] S3, performing negative pressure treatment and heating treatment on the second pole piece;

[0016] Wherein, the porous material contains the metal element M; and / or the liquid sodium-potassium alloy also contains the metal element M;

[0017] The metal element M is selected from one of Group IIA and Group IIIA.

[0018] Optionally, the viscosity of the slurry is 50~20000Cp; and / or, the solid content of the slurry is 5~80%; and / or, based on the total weight of the slurry, the content of the porous material is 10~50wt.%; and / or, the slurry also contains a binder and a negative electrode solvent, the binder includes at least one of polyvinylidene fluoride, polymethyl methacrylate, polyvinyl alcohol and polycaprolactam, and the negative electrode solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide and acetone.

[0019] Optionally, in the current collector coated with the slurry, the coating surface density of the porous material is 0.1-1 mg / cm 2 .

[0020] Optionally, in step S1, the conditions for the drying treatment include: a temperature of 80~120°C and a time of 90~100 min; and / or, in step S3, the pressure of the negative pressure treatment is -300~-20 kPa; and / or, the heating treatment is carried out under negative pressure conditions, and the conditions for the heating treatment include: a temperature of 100~500°C, a time of 30~180 min, and a pressure of -300~-20 kPa.

[0021] A third aspect of the present invention provides a battery, the battery comprising a negative electrode plate, the negative electrode plate comprising the above-mentioned negative electrode plate or a negative electrode plate prepared according to the above-mentioned preparation method.

[0022] Through the above technical solution, the beneficial technical effects of the present invention are:

[0023] (1) The negative electrode plate of the present invention includes a negative electrode active material layer, which includes a porous material and an alloy material filled in the pores of the porous material, wherein the alloy material includes a Na-KM ternary alloy. The negative electrode active material layer can effectively inhibit sodium crystallization and widen the liquid window. The Na-KM ternary alloy of the present invention has ultra-high surface tension and an ultra-wide alloy molar ratio window. The addition of the metal element M can widen the liquid molar window of the sodium-potassium alloy, reduce the freezing point, and maintain the liquid state at a lower temperature, so that the sodium-potassium alloy negative electrode can be used at low temperatures.

[0024] (2) In the negative electrode sheet of the present invention, by using a Na-KM ternary alloy with higher density and viscosity, the surface tension of the alloy material can be increased, the fluidity can be reduced, and the physical stability of the negative electrode sheet can be improved.

[0025] (3) The negative electrode plate of the present invention has a high energy density. The sodium metal content in the negative electrode plate of the present invention is higher than that of potassium metal, and for a unit mole of the positive electrode of the sodium ion battery, only a small amount of alloy material is required to ensure the stable cycle of the electrochemical reaction process, which greatly reduces the mass and volume of the negative electrode, thereby increasing the volume energy density and mass energy density.

[0026] (4) In the preparation method of the present invention, liquid sodium-potassium alloy is used to coat the surface of the first electrode away from the current collector. The liquid sodium-potassium alloy has ultra-high surface tension and ultra-wide alloy molar ratio window. On the one hand, it can ensure the sodium ions required for the electrochemical reaction process and always maintain a liquid state with high surface tension, so that sodium dendrites cannot grow; on the other hand, it can ensure that the electrochemical reaction process is carried out stably in a cycle, greatly reducing the mass and volume of the negative electrode, thereby increasing the volume energy density and mass energy density.

[0027] (5) The negative electrode plate of the present invention has a high energy conversion efficiency and a small volume change. In the preparation method of the present invention, after sodium ions obtain electrons on the surface of the sodium-potassium alloy and become sodium element, they are quickly and evenly distributed in the phases of the sodium-potassium alloy body by means of the alloying reaction of the sodium-potassium alloy, and no reaction heat effect of the insertion-extraction reaction and the conversion reaction is generated, thereby increasing the energy conversion efficiency. Sodium ions obtain electrons on the surface of the sodium-potassium alloy and enter the phases of the sodium-potassium alloy body, which does not cause a large volume expansion of the material and has a small volume change.

[0028] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.

[0030] Figure 1 The negative electrode sheet prepared in Example 1 is shown.

[0031] Figure 2 The second pole piece prepared in Example 1 is shown. DETAILED DESCRIPTION

[0032] The present invention discloses a negative electrode plate and a method for preparing the same and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0033] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0034] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0035] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0036] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0037] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0038] In order to solve the problem of low energy density of sodium ion batteries in the prior art, the present invention adopts the following technical solution:

[0039] A first aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising a current collector and a negative electrode active material layer disposed on the surface of the current collector; the negative electrode active material layer comprises a porous material and an alloy material filled in the pores of the porous material;

[0040] Wherein, the alloy material comprises a Na-KM ternary alloy, and the metal element M contained in the Na-KM ternary alloy is selected from one of group IIA and group IIIA.

[0041] The negative electrode plate of the present invention includes a negative electrode active material layer, which includes a porous material and an alloy material filled in the pores of the porous material, wherein the alloy material includes a Na-KM ternary alloy, which can effectively inhibit sodium crystallization and widen the liquid window. Specifically, the alloy material of the present invention has an ultra-high surface tension and an ultra-wide alloy molar ratio window. The addition of the metal element M can widen the liquid molar window of the sodium-potassium alloy, reduce the freezing point, and maintain the liquid state at a lower temperature, so that the sodium-potassium alloy negative electrode can be used at low temperatures (for example, below 20°C).

[0042] According to the present invention, by using a Na-KM ternary alloy with higher density and viscosity, the surface tension of the alloy material can be increased, the fluidity can be reduced, and the physical stability of the negative electrode sheet can be improved. In the Na-KM ternary alloy, if the content of metallic sodium is too low, it may not be enough to provide the sodium ions required for charging and discharging; if the content of metallic sodium is too high, it may cause the freezing point of the alloy to rise, which is not enough to form a liquid to resist sodium dendrites. In the present invention, the metal Na and metal K contained in the Na-KM ternary alloy can satisfy the relationship: 0.2≤n1 / (n1+n2)≤0.9, wherein n1 represents the amount of the metal Na contained in the Na-KM ternary alloy, and n2 represents the amount of the metal K contained in the Na-KM ternary alloy. At this ratio, the sodium ions required for the electrochemical reaction process can be guaranteed, and the liquid state with high surface tension is always maintained, so that sodium dendrites cannot grow. As a preferred embodiment of the present invention, the metal Na and the metal K contained in the Na-KM ternary alloy satisfy the relationship: 0.3≤n1 / (n1+n2)≤0.9.

[0043] According to the present invention, the content of the suitable metal element M in the Na-KM ternary alloy further broadens the liquid molar window of the sodium-potassium alloy, and the solidification point of the ternary alloy is lower, and the liquid state can be maintained at a lower temperature, so that the sodium-potassium alloy negative electrode can be used at low temperatures. In the present invention, based on the total mass of the Na-KM ternary alloy, the content of the metal element M can be 0.001~10wt.%. Exemplarily, the content of the metal element M can be any value in 0.001wt.%, 0.1wt.%, 1wt.%, 2wt.%, 4wt.%, 6wt.%, 8wt.% and 10wt.%, or any value in the range of any two of the above values. If the content of the suitable metal element M in the Na-KM ternary alloy is too low, it will not be able to achieve the effect of broadening the liquid temperature window; if the content of the suitable metal element M in the Na-KM ternary alloy is too high, the energy density of the system will be reduced. Preferably, based on the total mass of the Na—KM ternary alloy, the content of the metal element M may be 1-3 wt.%.

[0044] In a preferred embodiment of the present invention, the metal element M may be selected from one of Mg, Al, Ca, Sr, Ba and Ga.

[0045] According to the present invention, the Na-KM ternary alloy has a larger density and viscosity. Compared with the sodium-potassium alloy, the surface tension is further increased and the fluidity is reduced. The Na-KM ternary alloy is applied to the negative electrode plate to improve the physical stability of the material. The viscosity of the Na-KM ternary alloy can be 100~50000Cp. Exemplarily, the viscosity of the Na-KM ternary alloy can be any value among 100Cp, 1000Cp, 5000Cp, 10000Cp, 20000Cp, 30000Cp, 40000Cp and 50000Cp or any value within the range of any two of the above values. In the present invention, if the viscosity of the Na-KM ternary alloy is too high, it may increase the difficulty of alloy infusion during the preparation process; if the viscosity of the Na-KM ternary alloy is too low, it may be too fluid for the alloy to adhere to the porous material. Preferably, the viscosity of the Na-KM ternary alloy may be 20000-30000 Cp.

[0046] According to the present invention, the content of suitable porous material in the negative electrode active material layer has the effect of high capillary adsorption. In the present invention, based on the total mass of the negative electrode active material layer, the content of the porous material can be 1~2wt.%. Exemplarily, based on the total mass of the negative electrode active material layer, the content of the porous material can be any value of 1wt.%, 1.2wt.%, 1.4wt.%, 1.6wt.%, 1.8wt.% and 2wt.%, or any value within the range of any two of the above values. In the present invention, if the content of the porous material is too high, it may result in the inability to form a uniform and thin coating; if the content of the porous material is too low, it may result in a reduction in the amount of sodium-potassium alloy that can be stored, thereby increasing the thickness of the finished product and reducing the volume energy density of the system. Preferably, based on the total mass of the negative electrode active material layer, the content of the porous material can be 1.5~1.75wt.%.

[0047] Illustratively, the porous material may be selected from at least one of ZnO, SnO, vermiculite and boehmite.

[0048] In the present invention, the contact portion between the alloy material and the porous material has an oxide layer, and the oxide layer includes sodium oxide and / or potassium oxide. The oxide layer can isolate the Na-KM ternary alloy from the porous material, thereby isolating the Na-KM ternary alloy from further reaction with trace metal elements in the porous material.

[0049] A second aspect of the present invention provides a method for preparing a negative electrode sheet, the method comprising the following steps:

[0050] S1, coating a slurry containing a porous material on the surface of a current collector to obtain a current collector coated with the slurry; drying the current collector coated with the slurry to obtain a first pole piece;

[0051] S2, coating a liquid sodium-potassium alloy on a surface of the first pole piece away from the current collector to obtain a second pole piece;

[0052] S3, performing negative pressure treatment and heating treatment on the second pole piece;

[0053] Wherein, the porous material contains the metal element M; and / or the liquid sodium-potassium alloy also contains the metal element M;

[0054] The metal element M is selected from one of Group IIA and Group IIIA.

[0055] In the preparation method of the present invention, liquid sodium-potassium alloy is coated on the surface of the first pole piece away from the current collector, and the capillary effect of the porous material is used to generate capillary force, and the liquid alloy enters the porous material through negative pressure and high temperature treatment. The liquid sodium-potassium alloy in the present invention has ultra-high surface tension and ultra-wide alloy molar ratio window. On the one hand, it can ensure the sodium ions required for the electrochemical reaction process, and always maintain a liquid state with high surface tension, so that sodium dendrites cannot grow; on the other hand, it can ensure that the electrochemical reaction process is carried out in a stable cycle, greatly reducing the mass and volume of the negative electrode, thereby increasing the volume energy density and mass energy density.

[0056] In the present invention, the addition of the metal element M can broaden the liquid molar window of the sodium-potassium alloy, reduce the freezing point, and maintain the liquid state at a lower temperature, so that the sodium-potassium alloy negative electrode can be used at low temperatures.

[0057] In one embodiment of the present invention, the porous material contains a metal element M. Exemplarily, the porous material may be vermiculite, which contains a trace amount of MgO. Na and K are strong reducing metals with higher metal activity than Mg, and can undergo redox reactions with MgO to generate NaO and K2O and metallic Mg. NaO and K2O are more chemically stable and adhere to the surface of vermiculite to isolate the sodium-potassium alloy from further reaction with MgO. Mg can form a Mg-Na-K ternary alloy with Na and K.

[0058] In another embodiment of the present invention, the liquid sodium-potassium alloy contains the metal element M. The negative electrode sheet of the present invention is obtained by coating the liquid sodium-potassium alloy containing the metal element M on the surface of the first electrode sheet away from the current collector, and then subjecting the surface to negative pressure treatment and heat treatment.

[0059] In the present invention, the viscosity of the slurry may be 50 to 20000 Cp. Exemplarily, the viscosity of the slurry may be any value among 50 Cp, 100 Cp, 150 Cp, 200 Cp, 1000 Cp, 5000 Cp, 10000 Cp, 15000 Cp and 20000 Cp or any value within the range of any two of the above values. Preferably, the viscosity of the slurry may be 50 to 200 Cp.

[0060] In the present invention, the solid content of the slurry may be 5-80%. For example, the solid content of the slurry may be any value among 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70% and 80%, or any value within the range of any two of the above values. Preferably, the solid content of the slurry may be 25-30%.

[0061] In the present invention, based on the total weight of the slurry, the content of the porous material may be 10-50wt.%. Exemplarily, based on the total weight of the slurry, the content of the porous material may be any value among 10wt.%, 20wt.%, 30wt.%, 40wt.% and 50wt.%, or any value within the range of any two of the above values. Preferably, based on the total solid weight of the slurry, the content of the porous material may be 20-30wt.%.

[0062] In a preferred embodiment of the present invention, vermiculite can be used as a porous material and heated under sealed vacuum conditions. The volume of the vermiculite material expands, and the negative pressure between the bulk phases generated by the hollow structure with a high number of capillaries accompanying the volume expansion causes the sodium-potassium alloy to be absorbed into the bulk phases after the vermiculite is expanded. In addition, the strong adsorption characteristics formed by the high capillary action after the vermiculite is expanded allow the sodium-potassium alloy to be stably adsorbed between the bulk phases.

[0063] According to the present invention, the slurry may further contain a binder and a negative electrode solvent.

[0064] Exemplarily, the binder may include at least one of polyvinylidene fluoride, polymethyl methacrylate, polyvinyl alcohol, and polycaprolactam, and the negative electrode solvent may include at least one of N-methylpyrrolidone, N,N-dimethylformamide, and acetone.

[0065] According to the present invention, in the current collector coated with the slurry, the coating surface density of the porous material can be 0.1-1 mg / cm 2 At this coating surface density, a negative electrode sheet with a suitable energy density can be obtained. If the coating surface density is too high, the energy density of the obtained negative electrode sheet will be reduced. For example, the content of the porous material can be 0.1 mg / cm 2 , 0.2 mg / cm 2 , 0.3 mg / cm 2 , 0.4 mg / cm 2 , 0.5 mg / cm 2 , 0.6 mg / cm 2 , 0.7mg / cm 2 , 0.8 mg / cm 2 , 0.9mg / cm 2 and 1 mg / cm 2 Preferably, the coating surface density of the porous material can be 0.2-0.5 mg / cm 2 .

[0066] According to the present invention, in step S1, the conditions for the drying treatment may include: a temperature of 80 to 120°C and a time of 90 to 100 min; and / or, in step S3, the pressure of the negative pressure treatment may be -300 to -20 kPa; and / or, the heating treatment is preferably carried out under negative pressure conditions, and the conditions for the heating treatment may include: a temperature of 100 to 500°C, a time of 30 to 180 min, and a pressure of -300 to -20 kPa.

[0067] A third aspect of the present invention provides a battery, the battery comprising a negative electrode plate, the negative electrode plate comprising the above-mentioned negative electrode plate or a negative electrode plate prepared according to the above-mentioned preparation method.

[0068] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.

[0069] Example 1

[0070] High expansion vermiculite and polyvinylidene fluoride were mixed in a mass ratio of 98:2 to obtain a first mixed material. 2 g of the first mixed material was weighed, and N-methylpyrrolidone was used as a solvent to prepare a slurry with a solid content of 30%, which was coated on the surface of a copper foil to obtain a copper foil coated with the slurry. The coating surface density of the high expansion vermiculite was 0.5 mg / cm 2 , the copper foil coated with the slurry was dried at 60° C. for 12 h to obtain the first electrode.

[0071] Metallic sodium and metallic potassium were mixed at a molar ratio of 6.5:3.5 to obtain a second mixed material. 2 g of the second mixed material was weighed, and the kerosene and oxide layer on the surfaces of the sodium and potassium were removed in a glove box, and the mixture was placed in a beaker. The beaker was shaken at room temperature for 5 minutes, and the shaking was stopped after the sodium and potassium formed a liquid alloy, and the mixture was set aside for later use.

[0072] Place the first pole piece inside the vacuum box, and evenly coat the surface of the coating on the first pole piece with liquid sodium-potassium alloy to obtain a second pole piece coated with liquid sodium-potassium alloy. Close the vacuum box, evacuate to -100 kPa, and then heat the inside of the vacuum box to 300°C for 2 hours. After the temperature of the vacuum box drops to room temperature, take out the pole piece to obtain the negative pole piece of this embodiment. The second pole piece in this embodiment is as shown in FIG. Figure 2 As shown, the negative electrode sheet finally prepared in this embodiment is as follows Figure 1 As shown. Figure 2 It can be seen that the vermiculite coating in the second pole piece before being heated, expanded and absorbing the liquid sodium-potassium alloy is a black coating, and the sodium-potassium alloy cannot exist stably on the coating surface and is in a liquid flowing state. Figure 1It can be seen that after the vermiculite layer expands and absorbs the sodium-potassium alloy after heating, the sodium-potassium alloy exists stably on the electrode and no longer flows, indicating that the liquid absorption characteristics brought about by the strong capillary action after the expansion of the vermiculite stably adsorb the liquid sodium-potassium alloy between the expanded vermiculite bodies. This structure can not only fix the sodium-potassium alloy, but also rely on the good contact between the liquid sodium-potassium alloy and the current collector to enhance the electronic conductivity.

[0073] Example 2

[0074] The preparation method of the negative electrode plate of this embodiment is generally the same as that of Embodiment 1, except that high expansion vermiculite and polyvinylidene fluoride are mixed in a mass ratio of 80:20.

[0075] Example 3

[0076] The preparation method of the negative electrode plate of this embodiment is generally the same as that of Embodiment 1, except that high expansion vermiculite and polyvinylidene fluoride are mixed in a mass ratio of 99.5:0.5.

[0077] Example 4

[0078] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that the coating surface density of the high expansion vermiculite is 1 mg / cm 2 .

[0079] Example 5

[0080] The preparation method of the negative electrode sheet of this embodiment is the same as that of embodiment 1, except that the coating surface density of the high expansion vermiculite is 0.1 mg / cm 2 .

[0081] Example 6

[0082] The preparation method of the negative electrode plate of this embodiment is generally the same as that of Embodiment 1, except that the molar ratio of the mixture of metallic sodium and metallic potassium is 9:1.

[0083] Example 7

[0084] The preparation method of the negative electrode plate of this embodiment is generally the same as that of Embodiment 1, except that the molar ratio of the mixture of metallic sodium and metallic potassium is 3:7.

[0085] Comparative Example 1

[0086] Metallic sodium and metallic potassium were mixed at a molar ratio of 6.5:3.5 to obtain a second mixed material. 2 g of the second mixed material was weighed, and the kerosene and oxide layer on the surfaces of the sodium and potassium were removed in a glove box, and the mixture was placed in a beaker. The beaker was shaken at room temperature for 5 minutes, and the shaking was stopped after the sodium and potassium formed a liquid alloy, and the mixture was set aside for later use.

[0087] The liquid alloy is evenly spread on the surface of the copper foil to obtain the negative electrode sheet of this comparative example.

[0088] Comparative Example 2

[0089] The preparation method of the negative electrode sheet of this comparative example is generally the same as that of Example 1, except that porous carbon is used instead of vermiculite.

[0090] Test Example 1

[0091] The negative electrode sheets prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were cut to obtain negative electrode sheets of 100 mm×55 mm. Batteries were prepared from the negative electrode sheets, and the electrochemical performance of the batteries was tested. The test results are shown in Table 1.

[0092] Among them, the preparation method of the battery includes: using sodium vanadium iron phosphate as the positive electrode active material, mixing it with a conductive agent, a binder, etc., coating it on an aluminum foil, and making a positive electrode sheet through drying, pressing and other processes. The size of the positive electrode sheet is 96mm×51mm. A glass fiber diaphragm is used as a diaphragm. The electrolyte is 1M NaClO4, dissolved in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. The assembly process adopts a soft pack lamination method for assembly.

[0093] Stacking: Stack the positive electrode sheet, separator, and negative electrode sheet in order to obtain a battery cell.

[0094] Assembly: Heat-press the stacked cells and place them in aluminum-plastic film for top and side sealing.

[0095] Injection: inject electrolyte into the battery. Packaging: seal the battery after injection, injection coefficient 3g / Ah.

[0096] Formation: The packaged battery is subjected to formation treatment. When comparing the electrochemical performance of different positive electrode sheets, the negative electrode load is basically the same. Set the charge and discharge cut-off voltage to 2.5~4.0V, the charge and discharge current to 1A / g, and end the test after 200 cycles.

[0097] The test methods for electrochemical performance testing include:

[0098] (1) Energy efficiency test method: After the battery is manufactured, it is first charged to 3.75V at a constant current of 0.1C to obtain the formation capacity C0. Then the battery is divided into different capacities, charged to 4.0V at a constant current of 0.33C, and then charged to I≤0.05C at a constant voltage of 4.0V to obtain the battery energy E1 after the capacity division. After standing for 5 minutes, the battery is discharged to 2.5V at a constant current of 1C to obtain the discharge energy E2, and then charged to 4.0V at a constant current of 1C to obtain the charging energy E3. The energy efficiency is calculated as (E3 / E2*)100%.

[0099] (2) 1000-cycle capacity retention rate test method: 1. After the capacity division is completed, the battery is first charged to 4.0V at a constant current of 1C, and then charged to I≤0.05C at a constant voltage of 4.0V; 2. After standing for 5 minutes, the battery is discharged to 2.5V at a constant current of 1C to obtain the discharge capacity C1; 3. Stand for 30 minutes. Repeat steps 1-3 999 times to obtain the discharge capacity C 1000 ; 1000 cycles capacity retention rate according to (C 1000 ) / (C1)*100%.

[0100] (3) Low temperature test: The energy efficiency of Example 1 and Comparative Example 1 at 0°C and the capacity retention rate after 1000 cycles were tested.

[0101] Table 1

[0102]

[0103] It can be seen from Table 1 that the negative electrode sheet prepared by the embodiment of the present invention has significantly improved energy efficiency and capacity retention rate. By comparing Examples 1 to 3, it can be seen that changing the content of porous material in the slurry will change the energy efficiency and 1000-cycle capacity retention rate of the battery. The slurry in Example 1 contains 29.4wt% of high-expansion vermiculite. The battery prepared by the negative electrode sheet of Example 1 can achieve better energy efficiency and 1000-cycle capacity retention rate. It can be seen from Examples 1, 4 and 5 that the coating surface density of the porous material has a certain influence on the energy efficiency and 1000-cycle capacity retention rate of the battery. The coating surface density of the high-expansion vermiculite in Example 1 is 0.5mg / cm 2 , the battery prepared using the negative electrode sheet of Example 1 can achieve better energy efficiency and capacity retention rate. It can be seen from Example 1, Example 6 and Example 7 that compared with Example 1, the increase in the content of metallic sodium in Example 6 may cause the solidification point of the alloy to increase, which is not enough to form a liquid to resist sodium dendrites, and the electrochemical properties have a significant decrease; the metallic sodium content in Example 7 is reduced, which is not enough to provide the sodium ions required for charging and discharging, and the electrochemical performance is significantly reduced. It can be seen from Example 1 and Comparative Example 1 that the use of vermiculite can effectively improve the energy efficiency and cycle capacity retention rate of the alloy negative electrode, indicating that the protective layer formed by the elements in vermiculite and the void structure of vermiculite have a positive effect on improving the cycle performance of sodium-potassium alloy. It can be seen from Example 1 and Comparative Example 2 that when porous carbon is used instead of vermiculite, that is, the metal element Mg is not added during the entire preparation process of the negative electrode sheet, the energy efficiency and 1000-cycle capacity retention rate of the battery are significantly reduced compared with Example 1.

[0104] Test Example 2

[0105] The negative electrode sheets prepared in Example 1 and Comparative Example 1 were made into batteries (the preparation method was the same as that in Test Example 1), and the low-temperature performance of the two groups of batteries was tested, wherein the low-temperature performance included the energy efficiency of the battery at 0°C and the capacity retention rate after 1000 cycles. The test results are shown in Table 2.

[0106] Table 2

[0107]

[0108] It can be seen from the data in Table 2 that the battery made from the negative electrode sheet of Example 1 can still have good energy efficiency and 1000-cycle capacity retention rate at low temperatures.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate includes a current collector and a negative electrode active material layer disposed on the surface of the current collector; the negative electrode active material layer includes a porous material and an alloy material filled in the pores of the porous material; Wherein, the alloy material includes a Na-KM ternary alloy, the Na-KM ternary alloy is a liquid alloy, and the metal element M contained in the Na-KM ternary alloy is selected from one of Mg, Al, Ca, Sr, Ba and Ga.

2. The negative electrode sheet according to claim 1, characterized in that: The metal Na and the metal K contained in the Na-KM ternary alloy satisfy the relationship: 0.2≤n1 / (n1+n2)≤0.9, wherein n1 represents the amount of the metal Na contained in the Na-KM ternary alloy, and n2 represents the amount of the metal K contained in the Na-KM ternary alloy; And / or, based on the total mass of the Na—KM ternary alloy, the content of the metal element M is 0.001-10 wt.%.

3. The negative electrode sheet according to claim 1, characterized in that: The viscosity of the Na-KM ternary alloy is 100-50000 Cp.

4. The negative electrode sheet according to claim 1, characterized in that: Based on the total mass of the negative electrode active material layer, the content of the porous material is 1-2 wt.%; And / or, the porous material is selected from at least one of ZnO, SnO, vermiculite and boehmite.

5. The negative electrode sheet according to claim 1, characterized in that: A contact portion of the alloy material with the porous material has an oxide layer, and the oxide layer includes sodium oxide and / or potassium oxide.

6. A method for preparing a negative electrode sheet, characterized in that: The preparation method comprises the following steps: S1, coating a slurry containing a porous material on the surface of a current collector to obtain a current collector coated with the slurry; drying the current collector coated with the slurry to obtain a first pole piece; S2, coating a liquid sodium-potassium alloy on a surface of the first pole piece away from the current collector to obtain a second pole piece; S3, performing negative pressure treatment and heating treatment on the second pole piece; Wherein, the porous material contains the metal element M; and / or the liquid sodium-potassium alloy also contains the metal element M; The metal element M is selected from one of Mg, Al, Ca, Sr, Ba and Ga; The heating treatment is performed under negative pressure conditions, and the conditions of the heating treatment include: temperature of 100-500° C., time of 30-180 min, and pressure of -300--20 kPa.

7. The preparation method according to claim 6, characterized in that: The viscosity of the slurry is 50~20000Cp; And / or, the solid content of the slurry is 5-80%; and / or, based on the total weight of the slurry, the content of the porous material is 10-50wt.%; And / or, the slurry further contains a binder and a negative electrode solvent, the binder includes at least one of polyvinylidene fluoride, polymethyl methacrylate, polyvinyl alcohol and polycaprolactam, and the negative electrode solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide and acetone.

8. The preparation method according to claim 6, characterized in that: In the current collector coated with the slurry, the coating surface density of the porous material is 0.1-1 mg / cm 2 .

9. The preparation method according to claim 6, characterized in that: In step S1, the drying conditions include: temperature of 80-120°C and time of 90-100 min; And / or, in step S3, the pressure of the negative pressure treatment is -300 ~ -20 kPa; and / or, the heating treatment is carried out under negative pressure conditions, and the conditions of the heating treatment include: temperature of 100~500°C, time of 30~180min, and pressure of -300~ -20 kPa.

10. A battery, characterized in that: The battery comprises a negative electrode plate, and the negative electrode plate comprises the negative electrode plate according to any one of claims 1 to 5 or the negative electrode plate prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Non-Newtonian fluid Na-K alloy electrode and preparation method and application thereof

    CN109244441A

  • Electrochemical material comprising solid phase and liquid phase

    CN114223082A